Dampak Media Sosial terhadap Penjualan Produk Usaha Mikro Kecil dan Menegah di Gerakan Pemuda Ansor Kecamatan Pagedangan Kabupaten Tangerang - Dewi Ningsih; Budi Ismanto; Ali Zaenal Abidin (Jurnal PKM Manajemen Bisnis, 2026)
The rapid development of social media has significantly transformed business marketing strategies, particularly for Micro, Small, and Medium Enterprises (MSMEs). Social media platforms provide cost-effective and accessible opportunities for entrepreneurs to promote products, expand market reach, and improve customer engagement. However, many MSME actors still face challenges in utilizing social media effectively to support business growth. Therefore, a Community Service Program was conducted to enhance participants’ understanding and skills in digital marketing. The objective of this program was to increase awareness and competence among members of Gerakan Pemuda Ansor regarding the utilization of social media to improve product sales performance. The activity was carried out at Cicalengka Village Hall, Pagedangan District, Tangerang Regency, on May 19, 2026. The PKM team consisted of five lecturers from Pamulang University, involving 32 participants from Gerakan Pemuda Ansor. The implementation methods included presentations, hands-on practice, discussions, and question-and-answer sessions. The program was conducted through three stages: preparation, implementation, and reporting. The results indicated that participants gained a better understanding of social media marketing strategies, content creation techniques, and customer engagement practices. Participants also demonstrated increased motivation and readiness to utilize social media platforms to support business development and improve MSME product sales.